Achieving Amorphous Ultralong Room Temperature Phosphorescence by Coassembling Planar Small Organic Molecules with Polyvinyl Alcohol. (7th December 2018) - Wu, Hongwei; Chi, Weijie; Chen, Zhao; Liu, Guofeng; Gu, Long; Bindra, Anivind Kaur; Yang, Guangbao; Liu, Xiaogang; Zhao, Yanli
Abstract: Development of novel strategies for achieving amorphous ultralong organic phosphorescence (UOP) at room temperature is highly desired. Herein, a simple approach is reported by coassembling small organic molecules with polyvinyl alcohol (PVA) to afford amorphous UOP. These small organic molecules with planar conformation present quenched triplet state emission in an excessive stacking solid state. When coassembling these molecules with PVA, their planar structures are well confined in coassembly films. Such a confined environment leads to restricted molecular rotation and vibration, permitting these molecules to show stable triplet state and generate UOP. In control studies, corresponding structurally distorted molecules are also coassembled with PVA. However, they exhibit very weak or quenched UOP, since distorted structures with molecular rotation and vibration could easily dissipate the excitation energy in dilute film state. By employing this polymer confinement strategy, multicomponent luminescence dyes are further coassembled with PVA for multicolor luminescence displays, providing multicolor, uniform, and flexible luminescence films. This work demonstrates a general strategy of employing small organic molecules to coassemble with PVA to obtain amorphous UOP, which greatly expands the scope of organic molecules for developing simple but useful UOP films. Abstract : A general approach to afford amorphous ultralong organic phosphorescence (UOP) is developed by coassembling planar small organic molecules with polyvinyl alcohol (PVA). When coassembling these molecules with PVA, their planar structures are well confined in rigid coassembly films, permitting these molecules to show a stable triplet state and generate UOP.